« Chaque esprit est maçon » : l’Art Royal et l’idée de religion universelle dans la littérature française du XIXe siècle - Szymański, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
Masonic Royal Art, combining science and philosophy with spiritual research and moral improvement, radiates throughout the whole 19th century, which is the successor of both rationalist Enlightenment thought and 18th century illuminism. One of the key ideas of Freemasonry is the “Religion in which all Men agree” mentioned in Anderson’s Constitutions. The idea of a universal religion, referring to a primal revelation or taking the form of natural religion, has numerous variations in the 19th century, formed in contact with romantic literature (Madame de Staël), social utopias (Saint-Simonianism) or humanitarianism (Pierre Leroux). The aim of the article is to show the role played in this process by Freemasons and the influence they have exerted on other authors reflection on religion.